DEVELOPMENT OF LEARNING MEDIA WITH GEOGEBRA TO INCREASE STUDENTS LEARNING INTEREST ON FLAT-SIDED BUILDING MATERIALS - Dharma Satria Wijaya; Muhammad Isna Rosyada; Deni Hardianto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
GeoGebra is mathematics software that is packaged practically and is easy to use for learning and teaching at all levels of education. This research aims to determine the results of developing valid, practical and effective GeoGebra media on flat-sided geometric materials. This research was conducted at SDN Tukangan Yogyakarta. This research uses Research and Development procedures with the ADDIE development model of Analysis, Design, Development, Implementation, and Evaluation. The sampling technique used was purposive sampling. The subjects of this research were teachers and 27 class VI students. The data collection technique used was a questionnaire. The data collection instruments include material validation questionnaires, media validation questionnaires, practicality test questionnaires, and effectiveness test questionnaires. The data analysis technique uses descriptive analysis techniques, namely describing the data that has been collected. Research results: Validity tests carried out by media and materials experts produced scores of 2.4 and 2.8, both considered sufficient, so revisions were necessary. Furthermore, the revised GeoGebra learning media was tested individually, obtaining scores of 3.7 (very good) and 2.7 (fair) for 5 students and teachers. Field trials carried out by teachers and class VI students resulted in scores of 3.1 and 2.9, considered good in practice. Furthermore, the interest in learning questionnaire showed an increase from 45% to 69% in respondents who were classified as having good interest after using the media. In this way, GeoGebra learning media is validated, practical and effective.